Pricing Decision-Making Considering Ambiguity Tolerance in Consumers: Evidence from Recycled Building Material Enterprises - Jie Peng; Yuxi Zou; Hao Zhang; Lianghui Zeng; Yuhan Wang; Xingwei Li (Systems)
Globally, recycled building materials have attracted much attention, but the ambiguity of the use of recycled building materials makes it difficult for the building material remanufacturer (BMR) to compete with the building material manufacturer (BMM). Brand building is an important strategic tool for enterprises to increase product competitiveness. From the new perspective of the supply chain, this paper aims to examine the decision-making behavior of enterprises under two scenarios of consumer ambiguity neutrality and ambiguity tolerance and to analyze the impact of ambiguity tolerance on the pricing decisions of building materials supply chains in a brand-building scenario. This paper constructs a building material supply chain game model consisting of the BMM and BMR, according to the cognitive–affective personality system (CAPS) theory and through the Stackelberg game. The main findings are as follows. (1) Strengthening brand building can mitigate the negative impact of ambiguity tolerance on new product pricing. The selling price of recycled building materials is positively related to ambiguity tolerance. (2) When the BMM has higher brand value, there is a U-shaped trend between profit and ambiguity tolerance at a cost coefficient above the threshold value of 0.61. (3) When the BMR has higher brand value, profit is negatively related to ambiguity tolerance at operational inefficiencies and cost coefficients below the threshold value of 0.45. Otherwise, profits and ambiguity tolerance follow a U-shaped trend. This paper not only expands the research on brand building and ambiguity tolerance but also provides theoretical guidance for enterprises to make effective decisions in response to consumers’ ambiguity psychology.